2020
DOI: 10.4209/aaqr.2020.05.0202
|View full text |Cite
|
Sign up to set email alerts
|

Collection of SARS-CoV-2 Virus from the Air of a Clinic within a University Student Health Care Center and Analyses of the Viral Genomic Sequence

Abstract: The progression of COVID-19 worldwide can be tracked by identifying mutations within the genomic sequence of SARS-CoV-2 that occur as a function of time. Such efforts currently rely on sequencing the genome of SARS-CoV-2 in patient specimens (direct sequencing) or of virus isolated from patient specimens in cell cultures. A pilot SARS-CoV-2 air sampling study conducted at a clinic within a university student health care center detected the virus vRNA, with an estimated concentration of 0.87 virus genomes L-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 12 publications
(16 reference statements)
2
90
0
Order By: Relevance
“…In Wuhan (China) and Nebraska (US), SARS-CoV-2 nucleic acid tests conducted on air samples gave positive results at an intensive care unit of a hospital in Wuhan (China) and in a patient room of a university medical center in Nebraska (US) [ 17 , 18 ]. In Florida (US), SARS-CoV-2 was detected in air samples at the Student Health Care Center at the University of Florida via RT–PCR analysis [ 19 ]. In this study in Florida, the SARS-CoV-2 concentration was estimated to be 0.87 virus genomes/L air [ 19 ].…”
Section: Coronavirus Bioaerosolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Wuhan (China) and Nebraska (US), SARS-CoV-2 nucleic acid tests conducted on air samples gave positive results at an intensive care unit of a hospital in Wuhan (China) and in a patient room of a university medical center in Nebraska (US) [ 17 , 18 ]. In Florida (US), SARS-CoV-2 was detected in air samples at the Student Health Care Center at the University of Florida via RT–PCR analysis [ 19 ]. In this study in Florida, the SARS-CoV-2 concentration was estimated to be 0.87 virus genomes/L air [ 19 ].…”
Section: Coronavirus Bioaerosolsmentioning
confidence: 99%
“…In Florida (US), SARS-CoV-2 was detected in air samples at the Student Health Care Center at the University of Florida via RT–PCR analysis [ 19 ]. In this study in Florida, the SARS-CoV-2 concentration was estimated to be 0.87 virus genomes/L air [ 19 ]. Furthermore, in a study by Chia et al (2020) in Singapore, SARS-CoV-2 was detected in air samples from the airborne infection isolation rooms of infected patients via RT–PCR analysis and ORFlab assay [ 20 ].…”
Section: Coronavirus Bioaerosolsmentioning
confidence: 99%
“…In uenza A and B virus genomic RNAs were detected by RT-PCR directed at the HA and NA genes [6]. The primers and probes for the CDC 2019-Novel Coronavirus (2019-nCoV) rtRT-PCR test and an in-house (UF) test [7] ( Table 1) In-house developed Madin-Darby canine kidney (MDCK) cells that over-express α2-6-sialylglycan receptors [9] were to isolate in uenza viruses. As previously described [7], the African green monkey kidney cell line Vero E6, obtained from the American type culture collection (catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…A laboratory study showed that SARS‐CoV‐2 remained viable in aerosols throughout the duration of the experiment (3 h), with a reduction in infectious titre of 0.8 log 10 per litre of air (van Doremalen et al ., 2020). The results indicate that aerosol transmission of SARS‐CoV‐2 is possible, since the virus can remain viable and infectious in aerosols for hours, but transmission by aerosols has not been proven yet and a US study which found viral RNA in air samples could not infect cell cultures (Lednicky et al ., 2020). Another study showed that despite extensive environmental contamination, SARS‐CoV‐2 was not present in air samples obtained from the rooms of hospitalized patients with COVID‐19 (Rubens et al ., 2020).…”
Section: Persistence Of Sars‐cov‐2mentioning
confidence: 99%